AN ASSESSMENT OF MICROFINANCE INSTITUTION PERFORMANCE: The Importance of Institutional Environment - Arsyad, Lincolin (Gadjah Mada International Journal of Business, 2005)
This paper aims to assess the performance of Village Credit Institutions (Lembaga Perkreditan Desa or LPD) in Gianyar district, Bali province, Indonesia and its affecting factors âparticularly its institutional environment. The performance indicators assessed include financial indicators (such as portfolio quality, leverage, capital adequacy ratio, productivity, efficiency, profitability, and financial viability) and outreach of the LPDs. Institutions here refer to the rules or procedures that shape how agents (people) interact and the organizations that implement the rules and codes of conduct to achieve desired outcomes. Based on data from financial reports of 174 LPDs of Gianyar district in 1999 and 2001, interviews with some stakeholders (clients, chairmen, and member of commissioner board) of the LPDs, and using descriptive analysis approach, this paper reveals that the LPDs have achieved a good performance indicators and been sustainable, and the good performance and sustainability have been very much influenced by institutional environment which includes both formal and informal institutions.